A Discourse Analysis Of Online Bulletins In English And Vietnamese - Nguyễn Thị Huyền (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Undeniably, with the trend of globalization, people have to get information to know what is happening all over the world and bulletin is one of the rich sources of information. In this case, to avoid misunderstanding as well as confusion, we have to have some knowledge about discourse of a bulletin, this study carried out with a view to discover similarities and differences of English and Vietnamese bulletins. With the examples of English and Vietnamese bulletins collected, this thesis focuses on analyzing and comparing the syntactic and lexical features of bulletins. From the description as well as a full analysis on distinguishing features, we will draw their differences and similarities. It is hoped that the results of the study will serve as an access of a profound understanding of bulletin in English and Vietnamese. The study will help Vietnamese learners of English write good bulletins as well as to improve their writing skill.